Teacher-Driven Professional Learning as a Vehicle for Teacher Leadership: A Qualitative Study of Participant Leadership roles in Ontario's Teacher Learning and Leadership Program - Pamela Janie Osmond (Canadian Society for Studies in Education, 2014)
Over the past 20 years, a host of formalized teacher leadership programs have emerged in response to numerous calls for the re-culturing (Fullan, 2001) and re-professionalization (Hargreaves, 2000) of teaching. That being said, very little research has explored the manner in which such programs have facilitated real change in the leadership capacity of teachers. As such, the purpose of this study was to explore the nature and sustainability of leadership roles experienced by three participants in the Teacher Learning and Leadership Program (TLLP), a one-year program in Ontario, Canada, where teachers 'take the lead' in developing context specific professional learning opportunities with the aim of impacting both student and teacher learning. Results indicate that the TLLP provided participants with an avenue for the development and enactment of various teacher leadership opportunities both in and beyond their own school. However, extending that leadership beyond the timeframe of their TLLP projects proved to be a difficult endeavour. Understanding the impact of cultural norms, top-down hierarchies, and historical views of the teacher as implementer on the sustainability of teacher leadership is of particular relevance to planning committees who organize and develop such programs as well as progressive school boards who are genuinely interested in promoting authentic change in school leadership development.